Level of Vitamin D3 in Patients suffering from Knee Osteoarthritis.
Background: Worldwide decrease in Vit D3 level is major health issue which result multiple health problem because it exerts many eftect oti extrsescal ator system. and also contribute in multiple metabolism like mineral , cartilage etc. o its deficiency result many degenerative. metabolic and also aufoiinmune disorders. Osteoanhritisis chronic. degenerative. progressi ve infiammaiory disease wfiich resu[Is irre versible disable joint. As its nature is degenerative & progressive so corrirnonly fined in elder peoples either man or women. in ad vance stage due to distraction of cartilage and under line bone joints moments also restricted. Objectives: Aim of this rcscarch i‹i analyse level of 1 -25 dj (OH) Cholecalcilerol Via D 3 in patients with knee osteoarthritis I KOA). establish correlations with laboratory findings. Setting: PUMHS department of’ orthopedics and medicine OPD. Duration: 1" June 2017-31" May 2018 Design: cross sectional. Sample size: 200. Materials and 84ethods: 25-OH vitamin D3fD2 levels were assessed in serum samples of 200 padents as folios’s: 180 OA patients, and 20 healthy controls. Resets: Total patients of this smdy are 20t1 and controls; ; the mean age of patie fits was fi7.345D+6.2fi